A multifunctional HBED-type chelator with dual conjugation capabilities for radiopharmaceutical development - Makarem, Ata; Sarvestani, Mohammadreza K.; Klika, Karel D.; Kopka, Klaus (Synlett, 2019)
Bifunctional HBED chelators are hexadentate complexing ligands (chelators) that tightly coordinate to trivalent gallium and, additionally, are able to bind to bioactive molecules. In nuclear medicine, HBED-based radiopharmaceuticals are used as powerful radiotracers for tumor imaging. Among variants of bifunctional HBED chelators, HBED-CC is the most well-known; it possesses two terminal carboxylic acid groups that are able to undergo bioconjugation by amide-bond formation. However, to permit bioconjugation through click coupling, we previously modified the structure of HBED-CC and introduced HBED-NN chelator bearing two azide functions. We have now combined the conjugation capabilities of HBED-CC and HBED-NN chelators in one molecule and have created HBED-NC, which possesses both azide and carboxylic acid groups. The advantage of HBED-NC is that it provides options for constructing either monomeric or heterodimeric radiolabeling precursors. This work describes the synthesis of HBED-NC by either of two pathways.
Gesehen am 19.11.2019